Carrier localization in ZnO quantum wires - Kröger, Philipp; Ruth, Marcel; Weber, Nils; Meier, Cedrik (Applied Physics Letters)

Enhanced photoluminescence of colloidal nanocrystals embedded in epitaxially grown semiconductor microstructures - Kampmeier, J.; Rashad, M.; Woggon, U.; Ruth, M.; Meier, Cedrik; Schikora, D.; Lischka, K.; Pawlis, A. (Physical Review B)

Formation of defects in cubic GaN grown on nano-patterned 3C-SiC (001) - Kemper, R. M.; Häberlen, M.; Schupp, T.; Weinl, M.; Bürger, M.; Ruth, M.; Meier, Cedrik; Niendorf, T.; Maier, H. J.; Lischka, K.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report an anisotropic formation of defects in cubic GaN grown on nano-patterned 3C-SiC/Si (001) by molecular beam epitaxy. Nano-patterning of 3C-SiC/Si (001) is achieved by nanosphere lithography and a reactive ion etching process. Atomic force microscopy and scanning electron microscopy show that the selectivearea- grown cubic GaN nucleates in two structurally different domains, which most probably originate from the substrate. In adjacent domains the formation of defects, especially hexagonal inclusions, is different and leads to two different surface morphologies. The dominant phase within these domains was measured by electron backscatter diffraction. Optical properties were investigated by micro-photoluminescence and cathodoluminescence spectroscopy.

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, Cedrik (Optics Express)

Electrically driven intentionally positioned single quantum dot - Mehta, Minisha; Reuter, Dirk; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Zrenner, Artur; Meier, Cedrik (physica status solidi (c))
Using a combined all-ultra-high-vacuum process employing lateral patterning with focused ion beams and molecular beam epitaxy, site-selective growth of single (In,Ga)As quantum dots is achieved. We have embedded such a layer of intentionally positioned quantum dots in the intrinsic region of a p-i-n junction so that the quantum dots can be driven electrically. In this contribution, we will present our results on the morphological properties of the ion-beam modified surface on which the quantum dot nucleation occurs together with a characterization of the electrical and optoelectronic properties. We will demonstrate that a single, individual quantum dot can directly be electrically addressed.
Keywords: molecular beam epitaxy; quantum dot; site control; electroluminescence

Investigations on the director field around microdisc resonators - Urbanski, Martin; Piegdon, Karoline A.; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Liquid Crystals)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence

Controlled Etching Behavior of O-Polar and Zn-Polar ZnO Single Crystals - Mehta, M.; Meier, Cedrik (Journal of The Electrochemical Society)

Electroluminescence from silicon nanoparticles fabricated from the gas phase - Theis, Jens; Geller, Martin; Lorke, Axel; Wiggers, Hartmut; Wieck, Andreas; Meier, Cedrik (Nanotechnology)

Anticrossing of Whispering Gallery Modes in microdisk resonators embedded in an anisotropic environment - Declair, S.; Meier, Cedrik; Meier, Torsten; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the behavior of Whispering Gallery Modes (WGMs) in circularly shaped resonators like microdisks, with diameters in the range of optical vacuum wavelengths. The microdisk is embedded in an uniaxial anisotropic dielectric environment. By changing the optical anisotropy, one obtains spectral tunability of the optical modes. The degree of tunability strongly depends on the radial (azimuthal) mode order M (N). As the modes approach each other spectrally, anticrossing is observed, leading to a rearrangement of the optical states.
Keywords: tet_topic_microdisk

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
GaAs-based semiconductor microdisks with high quality whispering gallery modes (Q44000) have been fabricated.A layer of self-organized InAs quantumdots (QDs) served as a light source to feed the optical modes at room temperature. In order to achieve frequency tuning of the optical modes, the microdisk devices have been immersed in 4 – cyano – 4´-pentylbiphenyl (5CB), a liquid crystal(LC) with a nematic phase below the clearing temperature of TC≈34°C .We have studied the device performance in the temperature rangeof T=20-50°C, in order to investigate the influence of the nematic–isotropic phase transition on the optical modes. Moreover,we havea pplied an AC electric field to the device,which leads in the nematic phase to a reorientation of the anisotropic dielectric tensor of the liquid crystal.This electrical anisotropy can be used to achieve electrical tunability of the optical modes.Using the finite-difference time domain (FDTD) technique with an anisotropic material model, we are able to describe the influence of the liquid crystal qualitatively.
Keywords: tet_topic_qd; tet_topic_microdisk

Tuning quantum-dot based photonic devices with liquid crystals - Piegdon, Karoline A.; Declair, Stefan; Förstner, Jens; Meier, Torsten; Matthias, Heiner; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel; Meier, Cedrik (Optics Express)
Microdisks made from GaAs with embedded InAs quantum dots are immersed in the liquid crystal 4-cyano-4’-pentylbiphenyl (5CB). The quantum dots serve as emitters feeding the optical modes of the photonic cavity. By changing temperature, the liquid crystal undergoes a phase transition from the isotropic to the nematic state, which can be used as an effective tuning mechanism of the photonic modes of the cavity. In the nematic state, the uniaxial electrical anisotropy of the liquid crystal molecules can be exploited for orienting the material in an electric field, thus externally controlling the birefringence of the material. Using this effect, an electric field induced tuning of the modes is achieved. Numerical simulations using the finite-differences time-domain (FDTD) technique employing an anisotropic dielectric medium allow to understand the alignment of the liquid crystal molecules on the surface of the microdisk resonator.
Keywords: tet_topic_qd; tet_topic_microdisk

Inductively coupled plasma reactive ion etching of bulk ZnO single crystal and molecular beam epitaxy grown ZnO films - Mehta, M.; Ruth, M.; Piegdon, K. A.; Krix, D.; Nienhaus, H.; Meier, Cedrik (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Electron energy structure of self-assembled In(Ga)As nanostructures probed by capacitance-voltage spectroscopy and one-dimensional numerical simulation - Lei, Wen; Notthoff, Christian; Offer, Matthias; Meier, Cedrik; Lorke, Axel; Jagadish, Chennupati; Wieck, Andreas D. (Journal of Materials Research)

Ultrathin K∕p-Si(001) Schottky diodes as detectors of chemically generated hot charge carriers - Huba, K.; Krix, D.; Meier, Cedrik; Nienhaus, H. (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Silicon Nanoparticles: Excitonic Fine Structure and Oscillator Strength - Meier, Cedrik; Lüttjohann, Stephan; Offer, Matthias; Wiggers, Hartmut; Lorke, Axel (Advances in Solid State Physics)

Tunable optical properties of photonic crystals and semiconductor microdisks using liquid crystals - Piegdon, Karoline A.; Matthias, Heinrich; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Emerging Liquid Crystal Technologies III)